Progress of automatic driving technology and future information service architecture evolution of telecom operators - Zhen YANG (Dianxin kexue)
The concept of artificial intelligence has been proposed for more than 60 years，with the development of internet of things and big data technology，more and more AI technology applications have been achieved.One of the most remarkable AI technology integration application is automatic driving technology.Firstly，the progress of automatic driving technology was studied.Secondly，key technologies of automatic driving were analyzed.Thirdly， the relationship between the telecom operator information service architecture and the requirements of automatic driving was analyzed.In the end，the technology breakthrough point of information service architecture with the core of application of artificial intelligence technology in the future were given.